Teachers’ Preparedness and Students’ Learning: A Case of B.Ed. English Students at J.S. Murarka Multiple Campus, Lahan - Yadav, Ram Kumar Bhagat (Research Journal on Multi-disciplinary Issues, 2026)
This mixed-methods study explores the relationship between teacher preparedness and the learning outcomes of B.Ed. English students at J.S. Murarka Multiple Campus, Lahan, Nepal. Specifically, it examines how four domains of teacher preparedness; subject knowledge, pedagogical skills, classroom management, and ICT readiness that relate to students’ self-reported learning, engagement, and readiness to teach in school settings. The study draws on survey responses from 30 final-year B.Ed. English students and semi structured interviews with six teacher-educators, integrating quantitative and qualitative perspectives. Quantitative analysis reveals that pedagogical skills and classroom management are the strongest predictors of students’ learning, collectively explaining 46% of the variance (R² = .46, p < .001). Subject knowledge and ICT readiness, while positively associated with student outcomes, contribute less substantially. The qualitative findings provide rich contextual insights, highlighting barriers such as limited practicum opportunities, inadequate mentoring, insufficient in service professional development for teacher-educators, and restricted access to ICT infrastructure. These constraints hinder the translation of theoretical knowledge into practical classroom competence, affecting students’ confidence and engagement. The study underscores the importance of practice-oriented, student-centered pedagogical training and structured practicum experiences in enhancing teacher education outcomes in Nepal. By linking teacher preparedness directly to student learning, the research offers actionable, context-sensitive recommendations for policymakers and teacher education administrators seeking to strengthen the quality and effectiveness of B.Ed. programs in Nepal.